Karakteristik Gelatin dari Cangkang Kerang Hijau (Perna viridis) sebagai Alternatif Gelatin Halal - Hakim, Arief Rahman; Jumiono, Aji; Akil, Syahrir (Jurnal Ilmiah Pangan Halal, 2025)
The waste of green mussel shells has potential as an alternative source of halal gelatin; however, the efficiency of production and the physicochemical characteristics of the resulting gelatin remain underexplored. This study aims to examine the production process, characteristics, and quality of gelatin extracted from green mussel shells using acetic acid (0.75 M) over 3, 4, and 5 days. The study analyzed yield, moisture content, ash content, gel strength, and the physical characteristics of gelatin. The results indicate that a 4-day extraction duration produced an optimal yield of 1.57%, with low moisture and ash content and a gel strength of 340 gForce. All parameters met SNI standards, confirming the suitability of this gelatin for food, cosmetic, and pharmaceutical applications. These findings suggest that green mussel shells can be sustainably utilized to produce high-quality halal gelatin. The study implies opportunities for diversifying halal gelatin sources while supporting environmentally friendly waste management. Future research is encouraged to optimize the production process, expand product applications, and evaluate the environmental impacts of utilizing this waste.